Two Unusual Small Shelly Fossils from the Lower Cambrian of Southeastern Shaanxi Province, China. (March 2014) - Moore, John L.; Porter, Susannah M.; Li, Guoxiang
Abstract : Phosphatized and phosphatic small shelly fossils are a major source of information concerning the evolution of animals during the early Cambrian. Although progress has been made in understanding some of these fossils, many remain enigmatic, both with regard to their phylogenetic affinities and the overall morphology of the animal from which isolated sclerites came. Two unusual fossils from the upper lower Cambrian (Qiongzhusian or Atdabanian) Xihaoping Member of the Dengying Formation from Xiaowan, Xixiang County, southeastern Shaanxi Province, China are described herein. The first of these is a cap-shaped fossil we describe as Cambroskiadeion xiaowanense new genus and species. On its concave surface it bears a spine, the base of which is covered with numerous hemispherical verruculae. The long spine indicates that this was a sclerite rather than a univalved shell, although it remains unclear from what sort of animal it came. Similar fossils have been hypothesized to be halkieriid valves; although the rarity of halkieriid sclerites in the present samples argues against this view, it is possible these fossils are part of a similar multi-element skeleton. The second fossil is Acidocharacus longiconus Qin and Ding, 1988; it is known only from the Xihaoping Member and consists of a tall spine, often bearing barbs or bumps, attached to a rounded conical base. The base is covered with verruculae similar to those found on Cambroskiadeion . The function of these elements, and whether they were internal or external, remains unknown.